Plasma amyloid β levels are driven by genetic variants near APOE, BACE1, APP, PSEN2: A genome‐wide association study in over 12, 000 non‐demented participants. Issue 10 (18th May 2021) - Damotte, Vincent; van der Lee, Sven J.; Chouraki, Vincent; Grenier‐Boley, Benjamin; Simino, Jeannette; Adams, Hieab; Tosto, Giuseppe; White, Charles; Terzikhan, Natalie; Cruchaga, Carlos; Knol, Maria J.; Li, Shuo; et al.
Abstract: Introduction: There is increasing interest in plasma amyloid beta (Aβ) as an endophenotype of Alzheimer's disease (AD). Identifying the genetic determinants of plasma Aβ levels may elucidate important biological processes that determine plasma Aβ measures. Methods: We included 12, 369 non‐demented participants from eight population‐based studies. Imputed genetic data and measured plasma Aβ1‐40, Aβ1‐42 levels and Aβ1‐42/Aβ1‐40 ratio were used to perform genome‐wide association studies, and gene‐based and pathway analyses. Significant variants and genes were followed up for their association with brain positron emission tomography Aβ deposition and AD risk. Results: Single‐variant analysis identified associations with apolipoprotein E ( APOE ) for Aβ1‐42 and Aβ1‐42/Aβ1‐40 ratio, and BACE1 for Aβ1‐40. Gene‐based analysis of Aβ1‐40 additionally identified associations for APP, PSEN2, CCK, and ZNF397 . There was suggestive evidence for interaction between a BACE1 variant and APOE ε4 on brain Aβ deposition. Discussion: Identification of variants near/in known major Aβ‐processing genes strengthens the relevance of plasma‐Aβ levels as an endophenotype of AD.